2022
DOI: 10.3390/ijerph192416909
|View full text |Cite
|
Sign up to set email alerts
|

Relational Victimization and Video Game Addiction among Female College Students during COVID-19 Pandemic: The Roles of Social Anxiety and Parasocial Relationship

Abstract: Video game addiction, a common behavioral problem among college students, has been more prominent during the COVID-19 pandemic; at the same time, females’ video game usage has also attracted considerable research attention. Against this background and under the perspective of social interaction, this study aimed to examine the relationship between relational victimization and video game addiction among female college students, as well as its underlying mechanism—the mediating roles of social anxiety and paraso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…Several previous studies have explored the mechanism between victimization experiences and Problematic Internet Usage. For instance, a study conducted in China during the COVID-19 pandemic found that social anxiety acts as a mediator between relational victimization and video game addiction among female college students ( Niu et al, 2022 ). Additionally, another study demonstrated that psychological morbidity, such as depression and anxiety, serves as a mediating factor in the influence of victimization on problematic online behavior, including Internet Addiction and cyberbullying ( Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have explored the mechanism between victimization experiences and Problematic Internet Usage. For instance, a study conducted in China during the COVID-19 pandemic found that social anxiety acts as a mediator between relational victimization and video game addiction among female college students ( Niu et al, 2022 ). Additionally, another study demonstrated that psychological morbidity, such as depression and anxiety, serves as a mediating factor in the influence of victimization on problematic online behavior, including Internet Addiction and cyberbullying ( Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Over time, GST has been applied to understand a range of deviant behaviors, including alcohol abuse ( Swatt et al, 2007 ), excessive drug use ( Zweig et al, 2015 ) and problematic internet use among adolescents ( Shi and Wang, 2023 ). Moreover, the GST framework has been utilized to investigate the association between offline bully-victimization and cyberbullying behavior ( Jang et al, 2014 ), as well as between relational victimization and video game addiction among young individuals ( Niu et al, 2022 ). According to GST, individuals encounter various stressors (e.g., victimization experiences, VE) that disrupt their overall state of well-being and trigger emotional responses, including anger, frustration, or anxiety ( Agnew, 1985 ; Agnew and White, 1992 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some parents chose to allow their children more time on electronic devices ( Ayu Nuzulia et al, 2022 ). However, relieving negative emotions through this behavior may result in children’s addiction to electronic games ( Niu et al, 2022 ). At the same time, the lockdown had led many universities to move to online teaching formats and cancel social activities and structured physical exercises ( Rotnitsky et al, 2022 ); ( Tria, 2020 ).…”
Section: Challenges To the Dynamic Zero-covid Policymentioning
confidence: 99%
“…Meanwhile, studies have found that improper behavior of parents often results in parent-child conflicts and the deterioration of the parent-child relationship's quality, thereby weakening family functioning and cohesion [12,35]. Previous studies found that the COVID-19 pandemic has significantly changed people's lifestyles, including by precipitating decreased physical activity and increased reliance on online activities such as social media [43,44]. These lifestyle changes may contribute to an increase in phubbing behavior, leading to more family issues.…”
Section: The Mediating Role Of Parent-child Relationshipmentioning
confidence: 99%